2011
DOI: 10.1007/s10805-011-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

“If This is What I’m ‘Meant to be’…”: The Journeys of Students Participating in a Conversation Partner Scheme for People with Aphasia

Abstract: The development of speech language therapy students into clinicians is an area of increasing interest as educators focus on how knowledge, skills and attitudes are taught and learnt within the profession. The personal journeys of students through experiences of service learning have potential to further our understanding of the impact of civic engagement on the student experience and their learning. This paper explores the journeys of first year speech and language therapy students through a Thematic Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
(24 reference statements)
3
13
0
1
Order By: Relevance
“…Previous research has revealed that CPT with healthcare students can lead to self-reported increases in confidence communicating with PWA and increased recall of strategies for communicating effectively with PWA (Cameron et al, 2015;Jagoe & Roseingrave, 2011;McMenamin et al, 2015). The present study extended this body of research by revealing that participation in a CPT program can encourage speech-language pathology students to use effective communication behaviours during conversation with PWA.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous research has revealed that CPT with healthcare students can lead to self-reported increases in confidence communicating with PWA and increased recall of strategies for communicating effectively with PWA (Cameron et al, 2015;Jagoe & Roseingrave, 2011;McMenamin et al, 2015). The present study extended this body of research by revealing that participation in a CPT program can encourage speech-language pathology students to use effective communication behaviours during conversation with PWA.…”
Section: Discussionsupporting
confidence: 65%
“…It is possible that after receiving CPT the trained students felt more relaxed and more confident (as per Jagoe & Roseingrave (2011) and Wilkinson et al (2013)), and therefore, were more capable of focusing on the actual conversation and keeping the ideas flowing than the untrained students. This finding may also reflect that the students had learnt strategies for introducing new topics, or had benefitted from examples of conversation topics role modelled in the training.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature describes a global appraisal of conversation training approaches (Fox et al, 2009;Jagoe & Roseingrave, 2011;McVicker et al, 2009) In Phase 2 engaging representatives from all stakeholder groups in participatory dialogue using PLA techniques was a challenging task. It was difficult to negotiate and find times that suited representatives from all groups for face-to-face PLA sessions.…”
Section: R MC Menamin Et Al 2015mentioning
confidence: 99%
“…On one level the CPS gives aphasia experts an opportunity for purposeful involvement in a way that allows them to leave the "patient" behind; on another level, involvement appears to play an important role in redeveloping a positive self-identity. While bearing in mind the challenges of opening up participation opportunities for people with aphasia (e.g., Howe et al, 2008), our findings suggest that the UK CPS offers benefits to people with aphasia who may feel socially isolated , as well as to SLT students or health professionals, who have an opportunity for service learning and personal and professional development (Jagoe & Roseingrave, 2011). The implications for service provision are clear: people with aphasia do not just want to be "patients"; they wish to be actively involved and make a contribution.…”
Section: Resultsmentioning
confidence: 82%
“…A number of aspects of CPSs has been investigated, including the impact on those being visited and the experiences of students' learning and professional and personal development (Horton et al, 2007;Jagoe & Roseingrave, 2011). The impact of face-to-face interaction with individuals with embodied expertise is seen as a key feature of the experience for trainees in the health and social services (Skilton, 2011).…”
Section: Introductionmentioning
confidence: 99%